2005
DOI: 10.1158/1078-0432.ccr-04-2510
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of an Attenuated, Tumor-TargetingSalmonella typhimuriumto Dogs with Spontaneous Neoplasia: Phase I Evaluation

Abstract: Purpose: Genetically modified bacteria are a potentially powerful anticancer therapy due to their tumor targeting capacity, inherent antitumor activity, and ability to serve as efficient vectors for gene delivery. This study sought to characterize the acute and short-term toxicities and tumor colonization rates of a genetically modified Salmonella typhimurium (VNP20009) in dogs with spontaneous tumors, in the context of a phase I dose escalation trial. Experimental Design: Forty-one pet dogs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(111 citation statements)
references
References 37 publications
1
109
0
1
Order By: Relevance
“…Results of the Clostridium trial have recently been published (Roberts et al, 2014) and demonstrated an anti-tumor response. The preclinical studies of Clostridium also showed antitumor activity in a veterinary trial with pet dogs (Roberts et al, 2014) and an earlier study using Salmonella VNP20009 also showed significant antitumor activity in dogs with spontaneous neoplasms (Thamm et al, 2005). Continued success is likely to sustain interest in these novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Results of the Clostridium trial have recently been published (Roberts et al, 2014) and demonstrated an anti-tumor response. The preclinical studies of Clostridium also showed antitumor activity in a veterinary trial with pet dogs (Roberts et al, 2014) and an earlier study using Salmonella VNP20009 also showed significant antitumor activity in dogs with spontaneous neoplasms (Thamm et al, 2005). Continued success is likely to sustain interest in these novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 93%
“…However, in a human clinical study of lipid-modified Salmonella strain VNP20009 on patients with melanoma (ClinicalTrials.gov Identifier NCT00004988; Toso et al, 2002), there was no antitumor activity, even in patients that were confirmed to have the bacteria in their tumors. Despite the lack of success in humans, VNP20009 was shown to be effective against spontaneous neoplasms in dogs, including four complete responses and an overall response rate of 42% (Thamm et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Twenty patients received additional therapy after having failed prednisone/VBL, including surgery (n=12), RT (n=3), and medical therapy (n=12) (additional prednisone/ VBL, asparaginase, lomustine, vinorelbine, prednisone alone, dolastatin-10 [27] or genetically modified Salmonella [26]). Several dogs received more than one additional form of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Humans are not a natural host for S. typhimurium, and the elimination of lipid A prevents production of endotoxin (lipopolysaccharide), making these microorganisms nonvirulent. Because they have an acceptable safety profile (5,8) and are able to synthesize recombinant cytokines at high levels (9), we chose these bacteria for our studies, with a goal to explore the preclinical antitumor activity of S. typhimurium engineered to secrete cytokines. With the ability to grow anaerobically, we reasoned that S. typhimurium could grow even in hypoxic areas of tumors, which tend to be resistant to radiation or chemotherapy.…”
mentioning
confidence: 99%